Fuzzy measurements of a degree of destruction of professional skills at interruptions in training for operations in the emergency cases of flight - Невиніцин, А. М. (Proceedings of National Aviation University (archive), 2000)
The paper deals with the problem of definition of optimal and ultimate-acceptable interruptions in training for operations in emergency cases of flight. The theory of fuzzy sets is applied for this purpose and built are belonging functions of a linguistic variable "professional preparation level". For the 1st, 2nd and 3rd classes of air traffic controllers the optimal and ultimate-acceptable interruptions in learning are determined depending on the type of emergency case of flight